Melting characteristics of organic phase change material in a wavy trapezoidal cavity - Haddad, Zoubida; Iachachene, Farida; Öztop, Hakan Fehmi (Elsevier B.V., 2021)
Melting of n-eicosane in a wavy trapezoidal cavity heated from below is investigated numerically based on the enthalpy-porosity technique. The physical properties of n-eicosane are examined in details, and the impact of the amplitude of the wavy wall on the heat transfer and flow is discussed. The wave amplitude ranging is from 0 mm to 1.5 mm and the temperature difference range of 20–50 °C. The obtained results show that during the melting process, at low temperature difference, the rolls merge together, leading to a pair of larger and counter-rotating rolls. However, increasing the temperature difference for a = 1 mm and a = 1.5 mm causes the flow to become chaotic in time and space, where the rolls become irregular. The study also shows that the number of convection cells is time and wave dependent. Furthermore, it is observed that the melting time in the flat surface is about 2.5 times faster than that in the wavy surface at ?T = 50 °C. © 2021
Keywords: Heat transfer; Melting; Numerical simulation; Phase change material; Rayleigh-Bénard convection; Wavy trapezoidal cavity